Natural history and neurodevelopmental outcomes in perinatal stress induced hyperinsulinism - Sigal, Winnie M.; Alzahrani, Ohoud; Guadalupe, Gabriela M.; Guzman, Herodes; Radcliffe, Jerilynn; Thomas, Nina H.; Jawad, Abbas F.; De Leon, Diva D. (Frontiers in Pediatrics, 2022)
Objective: To describe perinatal stress induced hyperinsulinism (PSIHI), determine the prevalence of neurodevelopmental differences, and identify risk factors for poor developmental prognosis. Methods: Subjects with a history of hyperinsulinism (HI) and perinatal stress and in whom resolution of the HI was demonstrated were included. Medical record review, caregiver interview, and three validated developmental assessments were completed. Results: Of the 107 subjects (75% male), 36% were born between 32-37 weeks. Median age of hypoglycemia presentation was 0 days. Median age at HI diagnosis was 12 days (IQR 13.5). Median length of time for initiation of definitive treatment was 14 days (IQR 14). Caregiver interviews were completed for 53 of 79 eligible subjects. Developmental concerns were reported by 51%. Neurodevelopmental assessments were completed by caregivers of 37 of the 53 enrolled subjects. The proportion of subjects scoring > 1 SD and > 2 SD from the mean on the major composite scores was significantly greater than in the general population (40.5% vs. 15.8%, P ≤ 0.0001 and 18.9% vs. 2.2%, P ≤ 0.0001, respectively). Male sex, small for gestational age status (SGA), and treatment with continuous feeds were associated with assessment scores > 1 SD from the mean (P<0.05). SGA and preeclampsia were associated with assessment scores > 2 SD from the mean (P< 0.05). Conclusion: While the majority of infants presented with hypoglycemia in the first day of life, diagnosis and treatment occurred 12-14 days later. Children with PSIHI are at high risk of neurodevelopmental deficits and are more likely to perform below average on developmental assessment.